Geodynamics of the Latin American Pacific margin - Bandy, William L.; Dañobeitia, Juanjo; Gutiérrez, Carlos Mortera; Taran, Yuri; Bartolomé, Rafael (Birkhäuser, 2017)
Geodynamics of the Latin American Pacific Margin presents a collection of 22 studies by a multinational group of investigators whose common interest is to better understand the complex geodynamic processes occurring along the Pacific margin of Latin America and the impact that these processes have on the local populace. Processes investigated in these papers include the subduction of buoyant ridges and spreading centers, ophiolite emplacement, plate margin truncation, forearc deformation, mantle convection, magma emplacement and associated continental rifting, and the release of energy by great earthquakes as well as slow slip events. These studies illustrate the vast and varied research opportunities that exist along the margin, and will be a welcome addition to the library of those who are actively investigating the geodynamics of the Latin American Pacific margin as well as those interested in the subduction process in general.
"Previously published in Pure and Applied Geophysics (PAGEOPH), volume 173, no. 10-11, 2016."
Keywords: Geodynamics -- Latin America.; Latin America.; elektronické knihy; electronic books